Commensal bacteria augment Staphylococcus aureus infection by inactivation of phagocyte-derived reactive oxygen species. - Josie F Gibson; Grace R Pidwill; Oliver T Carnell; Bas G J Surewaard; Daria Shamarina; Joshua A F Sutton; Charlotte Jeffery; Aurélie Derré-Bobillot; Cristel Archambaud; Matthew K Siggins; Eric J G Pollitt; Simon A Johnston; et al. (PLoS Pathogens)
Staphylococcus aureus is a human commensal organism and opportunist pathogen, causing potentially fatal disease. The presence of non-pathogenic microflora or their components, at the point of infection, dramatically increases S. aureus pathogenicity, a process termed augmentation. Augmentation is associated with macrophage interaction but by a hitherto unknown mechanism. Here, we demonstrate a breadth of cross-kingdom microorganisms can augment S. aureus disease and that pathogenesis of Enterococcus faecalis can also be augmented. Co-administration of augmenting material also forms an efficacious vaccine model for S. aureus. In vitro, augmenting material protects S. aureus directly from reactive oxygen species (ROS), which correlates with in vivo studies where augmentation restores full virulence to the ROS-susceptible, attenuated mutant katA ahpC. At the cellular level, augmentation increases bacterial survival within macrophages via amelioration of ROS, leading to proliferation and escape. We have defined the molecular basis for augmentation that represents an important aspect of the initiation of infection.